Horticultural crops for export - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 2005)
Eric Kadenge talks to a French bean farmer and a mango farmer, and the extension worker who has been helping them, for example with record-keeping.